A single nucleotide polymorphism in dopamine beta hydroxylase (rs6271(C>T)) is over-represented in inflammatory bowel disease patients and reduces circulating enzyme - Gonzalez-Lopez, Eugene; Kawasawa-Imamura, Yuka; Zhang, Lijun; Huang, Xuemei; Koltun, Walter A.; Coates, Matthew D.; Vrana, Kent E. (PloS one, 2019)
Inflammatory bowel diseases (IBD) are associated with altered neuronal regulation of the gastrointestinal (GI) tract and release of norepinephrine (NE). As sympathetic innervation of the GI tract modulates motility, blood flow, and immune function, changes in NE signaling may alter the risk of developing IBD. Dopamine beta-hydroxylase (DβH), the enzyme responsible for NE production, has been suggested to play a critical role in IBD, however the exact mechanism is unknown. We hypothesized that genetic variants of DβH could increase the risk of IBD. We performed genetic analysis on 45 IBD patients and 74 controls. IBD patients were screened by targeted exome sequencing and compared with NeuroX DβH single nucleotide polymorphism (SNP) genotyping data of the controls. Serum DβH protein levels for 15 IBD patients and 13 controls were evaluated using immunoblots and competitive ELISA. Seven SNPs were observed from DβH targeted exome sequencing in the 45 IBD patients. A single non-synonymous SNP, rs6271 (Arg549Cys), had a significant association with IBD patients; the odds ratio was a 5.6 times higher SNP frequency in IBD patients compared to controls (p = 0.002). We also examined the function and availability of the protein in both the IBD and control patients' sera bearing DβH Arg549Cys. Both control and IBD subjects bearing the heterozygote allele had statistically lower DβH protein levels while the intrinsic enzyme activity was higher. This is the first report of a noradrenergic genetic polymorphism (rs6271; Arg549Cys) associated with IBD. This polymorphism is associated with significantly lower levels of circulating DβH.